Framing Sertifikasi Halal pada Konten Media Sosial TikTok dan Pengaruhnya terhadap Persepsi Pelaku UMKM - Atina Salsabila; Nikmatul Masruroh; Siti Raudhatul Jannah (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Halal certification has become an increasingly important issue for micro, small, and medium enterprises (MSMEs) in Indonesia, particularly as social media platforms such as TikTok are widely used to disseminate information about halal products. This study aims to examine how TikTok content frames the issue of halal certification and how such framing shapes the perception of MSME actors toward the importance of certification. Using a qualitative approach grounded in Entman’s framing theory, this research analyzes a purposive sample of TikTok videos discussing halal certification together with in-depth interviews involving MSME actors in the Jember area. The findings indicate that TikTok content tends to construct three dominant frames, namely an educational frame that emphasizes procedural knowledge, a religious-authority frame that links certification to religious obligation, and an economic-opportunity frame that highlights certification as a competitive advantage. These frames were found to significantly influence MSME actors’ awareness, trust, and motivation to pursue halal certification, although disparities in digital literacy still constrain the depth of understanding gained from short-form video content. The study concludes that strategic and easily digestible framing on social media can accelerate halal certification literacy among MSMEs, while also highlighting the need for more structured digital education to complement informal social media exposure.